Transformations of Urban Space on the Example of Modern Ijevan - Poghosyan, Vladimir (History and Culture, 2025)
The article is devoted to the study of the process of designing, forming, and transforming the urban space of Ijevan. The influence of the urban environment on social and cultural changes, the main trends, and the priorities of the Ijevan experience of designing urban space are studied. At the present stage of studying urban space, we consider it necessary to consider not only urban planning and architectural problems of urban space, but also to use this industry experience to examine the anthropological phenomenon and formats of the influence of urban space, in which the citizen and the (visually semiotic) environment formed around him are primary. From this point of view, we tried to consider the urbanization process of Ijevan as a factory where unique Soviet urban planning projects were implemented or conceived, the main trend of which was to provide a proportionate, harmonious urban space designed for everyone and everything. The current panorama of the urban space of Ijevan has been formed since the 1960s, and from a strategic perspective, it was planned that by 2000 the urban population would amount to more than 45 thousand people. Despite the significant urban heritage created during the Soviet era, in the first and second decades of independence, certain parts of the city (especially in the center) began to rebuild and adapt to market relations, resulting in a cultural heritage that is part of the urban space, entertainment facilities, and premises were given over to the public. Studying the experience of transforming the urban space of modern Ijevan provides a model opportunity to observe similar processes in other urban communities of the Republic.
Keywords: Ijevan; urban space; cultural strategy; urban planning; stability of borders; energy crisis; utopian project